2021
DOI: 10.3390/molecules26216469
|View full text |Cite
|
Sign up to set email alerts
|

Core-Level Spectroscopy of 2-Thiouracil at the Sulfur L1- and L2,3-Edges Utilizing a SASE Free-Electron Laser

Abstract: In this paper, we report X-ray absorption and core-level electron spectra of the nucleobase derivative 2-thiouracil at the sulfur L1- and L2,3-edges. We used soft X-rays from the free-electron laser FLASH2 for the excitation of isolated molecules and dispersed the outgoing electrons with a magnetic bottle spectrometer. We identified photoelectrons from the 2p core orbital, accompanied by an electron correlation satellite, as well as resonant and non-resonant Coster–Kronig and Auger–Meitner emission at the L1- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
(71 reference statements)
0
7
0
Order By: Relevance
“…25–29 Because of their high sensitivity to electronic and nuclear dynamics, AES/RAES are becoming increasingly popular techniques to unravel underlying electronic structure, 30 and nuclear dynamics of photoexcited molecules. 31–35…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25–29 Because of their high sensitivity to electronic and nuclear dynamics, AES/RAES are becoming increasingly popular techniques to unravel underlying electronic structure, 30 and nuclear dynamics of photoexcited molecules. 31–35…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28][29] Because of their high sensitivity to electronic and nuclear dynamics, AES/ RAES are becoming increasingly popular techniques to unravel underlying electronic structure, 30 and nuclear dynamics of photoexcited molecules. [31][32][33][34][35] RAES measurements of ozone have been obtained with photon energies of 530.8 and 536.7 eV, which correspond to the 1s O Tp*(2b 1 ) and 1s O Ts*(7a 1 ) excitations, 12,13 and at 542.3 eV, that lies near the 1s O Cs*(7a 1 ) excited state and above the 1s O T À1 ionization threshold. 13 For the case of the resonant 1s O Ts*(7a 1 ) state, a Doppler-type energy-split in the kinetic energy of atomic Auger electrons arising after fast fragmentation has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…This error can be immediately attributed to the limitations in our quantum chemistry approximation, even though we cannot discard photodissociation or other nuclear dynamical effects, which are ignored in our simulations. It is known that the RAES is very sensitive to nuclear relaxation processes. ,,, The inclusion of nuclear dynamic effects will be addressed in a further extension of this work aimed at time-resolved Auger simulations. For the moment, we retain ourselves to the analysis of the Auger spectra with the static ground-state equilibrium geometry.…”
Section: Resultsmentioning
confidence: 99%
“…The high sensitivity of AES/RAES to electronic and nuclear dynamics encouraged experimentalists to explore it to unravel underlying electron and nuclear dynamics of photoexcited molecules. In the case of halogen-containing molecules, the photoexcited repulsive σ* states expose the competition between nuclear dynamics and resonant Auger electron emission, because of the fact that both Auger decay and direct dissociation occur on the femtosecond time scale. In a series of recent studies, it was also demonstrated that ultrafast dissociation, distinguished by means of its fingerprint in the RAES, is a practical mechanism of distributing the molecular internal energy of the L -edge photoexcited systems in small molecules like HCl as well as in heavier ones, such as CH 2 Cl 2 and CHCl 3 . , Moreover, the Auger decay around the Cl 1s threshold of HCl has been recently simulated, considering the evolution of the relaxation process, including both electron and nuclear dynamics . Adding to that is the fact that AES does not obey the same dipole transition rules as XAS does, so AES/RAES can be used as a powerful tool to probe dark states and couple to nuclear dynamics. However, from the computational point of view, for AES/RAES to be used effectively as a probe of (excited-state) nuclear dynamics, one should efficiently deal with one of the major complications in the computation of Auger spectra, namely the description of the electron in the continuum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation